Effects of Intraoperative Neural Tunnel in Protecting Recurrent Laryngeal Nerve: Experiences in Open, Trans Breast, and Transoral Endoscopic Thyroidectomy - Yu, Xing; Li, Yujun; Liu, Chang; Jiang, Yuancong; Liu, Zhaodi; He, Qionghua; Wang, Yong; Wang, Ping (Frontiers in Oncology, 2022)
Background: Energy-based devices (EBDs) increase the risks of thermal nerve injuries. This study aimed to introduce a surgical strategy of intraoperative neural tunnel protecting (INTP) for evaluating the effect in reducing the incidence of recurrent laryngeal nerve (RLN) damage in open, trans breast, and transoral endoscopic thyroidectomy. Methods: INTP strategy was introduced: a tunnel was established and protected by endoscopic gauze along with the direction of nerve. 165, 94, and 200 patients with papillary thyroid carcinoma (PTC) were to use INTP in open, trans breast, and transoral endoscopic thyroidectomy as the INTP group. Additionally, 150, 95, and 225 patients who received the same methods without INTP were enrolled in the control group. Ipsilateral thyroidectomy or total thyroidectomy, and central compartment dissection were performed on the enrolled patients. Results: Clinicopathological characteristics, surgical outcomes, and surgical complications were similar between the INTP group and the control group in open, trans breast, and transoral endoscopic thyroidectomy respectively. The incidences of electromyography (EMG) changes in the INTP group were lower compared to the control group in trans breast endoscopic thyroidectomy (P < 0.05). Incidence of postoperative hoarse in INTP group was lower compared to the control group in open and transoral endoscopic thyroidectomy respectively (P < 0.05). Postoperative calcium levels (P < 0.01) were significantly higher, and the white blood cells (P < 0.05), C-reactive protein levels (P < 0.01) were significantly decreased in INTP group compared with the control in transoral endoscopic thyroidectomy. Conclusions: This was the first instance of the INTP strategy being introduced and was found to be an effective method for protecting RLN in open, trans breast, and transoral endoscopic thyroidectomy. Additionally, INTP helped protect other important tissues such as parathyroid glands in transoral endoscopic thyroidectomy as well as in reducing postoperative inflammatory responses.